Silver Nanoantibiotics Display Strong Antifungal Activity Against the Emergent Multidrug-Resistant Yeast Candida auris Under Both Planktonic and Biofilm Growing Conditions - Vazquez-Munoz, Roberto; Lopez, Fernando D.; Lopez-Ribot, Jose L. (Frontiers in Microbiology, 2020)
Candida auris is an emergent multidrug-resistant pathogenic yeast with an unprecedented ability for a fungal organism to easily spread between patients in clinical settings, leading to major outbreaks in healthcare facilities. The formation of biofilms by C. auris contributes to infection and its environmental persistence. Most antifungals and sanitizing procedures are not effective against C. auris, but antimicrobial nanomaterials could represent a viable alternative to combat the infections caused by this emerging pathogen. We have previously described an easy and inexpensive method to synthesize silver nanoparticles (AgNPs) in non-specialized laboratories. Here we have assessed the antimicrobial activity of the resulting AgNPs on C. auris planktonic and biofilm growth phases. AgNPs displayed a strong antimicrobial activity against all the stages of all C. auris strains tested, representative of four different clades. Under planktonic conditions, MIC values of AgNPs against the different strains were <0.5 µg mL -1 ; whereas calculated IC50 values for inhibition of biofilms formation were < 2 µg mL -1 for all but one of the C. auris strains tested. AgNPs were also active against preformed biofilms formed by all different C. auris strains, with IC50 values ranging from 1.2 to 6.2 µg mL -1 . Overall, our results indicate potent activity of AgNPs against strains of C. auris, both under planktonic and biofilm growing conditions and indicate that AgNPs may contribute to the control of infections caused by this emerging nosocomial threat.